Mental Capacity for Medical Treatment Decisions in Medical and Surgical Hospital Inpatients in Ireland - MURPHY, RUTH ANN (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2019)
Mental capacity both merits and requires substantial consideration and attention in present-day clinical practice, research and legislation. This is the first research study in the Republic of Ireland to evaluate the prevalence of mental capacity in general medical and surgical hospital inpatients, incorporating a considerable patient population (n=300) and including individuals from both an urban and rural catchment area in Ireland. The significant rate of mental incapacity in this cohort of individuals (27.7% of all study participants; n=83) indicates the frequency of this complex issue and furthermore, underscores the importance of commencing Ireland?s new mental capacity legislation, the Assisted Decision-Making (Capacity) Act 2015, which has been passed by Parliament and signed into law by President Michael D. Higgins, but to date awaits inauguration and implementation. Once executed and effected, this Act will provide imperative assistance and guidance to both healthcare and judicial staff in relation to all facets of the assessment, evaluation, determination and management of an individual?s mental capacity and capability to consent. As the rate of mental incapacity among general hospital inpatients in this Irish research study is essentially consistent with those reported in other international jurisdictions, there is undoubtedly a need to pay specific attention to this fundamental and imperative aspect of patient care, by promoting advance healthcare planning, by also devising national policies and protocols to be implemented when an individual lacks or may shortly mental capacity for medical treatment decisions and ultimately, to safeguard as much as is achievable, an individual?s right to autonomy during the inclusive decision-making process.
APPROVED
Keywords: Mental capacity; Hospital inpatients, Ireland; Medical legislation, Ireland; MacCAT-T